Increased occurrence of the jellyfish Periphylla periphylla in the European high Arctic - Geoffroy, Maxime; Berge, Jørgen; Majaneva, Sanna Kristiina; Johnsen, Geir; Langbehn, Tom; Cottier, Finlo Robert; Mogstad, Aksel Alstad; Zolich, Artur Piotr; Last, Kim (Polar Biology, 2018)
This is a post-peer-review, pre-copyedit version of an article published in Polar Biology . The final authenticated version is available online at https://doi.org/10.1007/s00300-018-2368-4 . The jellyfish Periphylla periphylla , which can have strong ecological impacts on its environment, is ubiquitous in the Norwegian Sea and its range was predicted to extend northwards. The occurrence of P. periphylla in the northern Barents Sea increased since 2014 and, for the first time, several individuals were collected within a high Arctic fjord (> 78°N) in western Spitsbergen in January 2017. The low solar irradiance prevailing during the polar night and an increased inflow of relatively warm Atlantic water in the European Arctic since the last decade likely provide suitable conditions for the medusa to colonize Svalbard’s fjords during the winter months. However, light avoidance constrains the photophobic P. periphylla to deeper offshore areas during the midnight sun period. The current occurrence of P. periphylla in high Arctic fjords during the polar night will have a limited impact on marine ecosystems in the short term, but long-term effects are more uncertain if its abundance continues to increase.